Outcomes of COVID-19 contact tracing in hospital healthcare workers: a retrospective cohort study - Durmaz, Seyfi; Kucuk, Ece Fidan; Simsek, Sera; Durgun, Kevser; Karakas, Emine Bilge; Durusoy, Raika (Journal of the Pakistan Medical Association, 2022)
Objective: To determine risk-group-specific rate of becoming COVID-19-positive among healthcare workers having had contact with COVID-19 cases. Methods: The retrospective cohort study was conducted at the Ege University Hospital, Bornova, Turkey, and comprised all healthcare workers who had come into contact with COVID-19 cases between March 11 and May 31, 2020. The contacts were classified as low-risk, medium-risk and high-risk using the guidelines of the Turkish Ministry of Health. The outcome measures were the incidence of infection among contacts and the incubation period and serial interval among the new cases. Data was analysed using SPSS 23. Results: Of the 845 cases, 312(37%) had high risk, 263(31%) medium and 270(32%) low. Overall, there were 490(58%) females, 355(41%) males, 565(67%) aged <40 years, and 277(33%) aged >40 years. Of the total, 27(3.20%) healthcare workers tested COVID-19-positive and distribution among the risk-based groups was significant (p=0.037). There was a significantly increased risk of incidence among repeated contacts, no mask use, and the source being a colleague (p<0.05). Conclusion: The detection of high-risk contacts was found to be important for controlling COVID-19 infection in a hospital setting. Key Words: SARS-CoV-2, Healthcare workers, Contact tracing, Contact-based surveillance. Continue...